Analisis Loyalitas Karyawan Pada Perusahaan JNE Express Di Denpasar, Provinsi Bali - Widiana, I Nyoman Wahyu (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
Human Resources (HR) are a mixture of energy, body, inspiration, talent, knowledge, creativity and expertise needed to move industry. This research aims to identify the influence of spirituality in the workplace, the influence of compensation and employee conflict on employee loyalty at the JNE Express company in Denpasar, Bali Province. This research uses a quantitative approach. The population and illustrations in this research are 34 employees at JNE Express. Methods for collecting information in this research include interviews, questionnaires, and library research. The information analysis method in this research uses multiple linear regression. Sourced from the research above. the influence of workplace spirituality has a positive and significant influence on employee loyalty in the JNE Express industry in Denpasar and compensation has a positive and significant influence on employee loyalty in the JNE Express industry in Denpasar, whereas work conflict has a negative and significant influence on employee loyalty in the JNE Express industry in Denpasar. workplace spirituality, compensation and work conflict simultaneously have a significant influence on employee loyalty in the JNE Express industry in Denpasar, Bali Province